PELATIHAN DASAR PEER COUNSELOR UNTUK SISWA PENDAMPING SANTRI DI PESANTREN KOTA JAMBI - Agung Iranda; Siti Raudhoh; Dessy Pramudiani; Marlita Andhika Rahman (Universitas Jambi, 2022)
ABSTRACT Students of Islamic boarding school (Pesantren) are teenagers in the transition phase from childhood into adulthood, who are vulnerable to conflict and psychological problems. For instance, negative influence from peers, sexual turmoil, juvenile delinquency, school or peer bullying might cause anxiety and social interaction difficult for teenagers. Therefore, it is important that peer counselor training be conducted at Pondok Pesantren Al-Jauharen and Al-As'ad Islamic boarding schools in Jambi Seberang, Jambi City. The implementation method is carried out in several steps, including determining the target area, surveying the target area, collecting data on participants, implementing activities, and evaluating activities. Peer counselor training activities with several sessions. First, brainstorming behaviors that need help. Second, games to increase the enthusiasm of participants. Third, lecturing about peer counseling, techniques in conducting peer counselors, as well as students' understanding in identifying which problems can be handled by students themselves, and which problems must involve professionals. Peer counselor training activities run effectively as planned, participants are very enthusiastic to follow each activity plan, and they are able to understand and apply peer counseling. Key word: Islamic boarding school, peer counselor, training ABSTRAK Para santri merupakan mereka yang menginjak fase remaja, dimana fase ini merupakan fase transisi dari anak-anak ke dewasa. Pada fase ini rentan terjadi permasalahan psikologis, diantaranya remaja mudah terbawa pengaruh negatif, gejolak seksual, kenakalan remaja, tindakan bullyng dari teman-teman mereka dalam satu lingkungan sekolah, yang membuat mereka sulit interaksi sosial dan cemas. Oleh karena itu, pentingnya pelatihan peer counselor yang akan dilakukan di Pondok Pasantren Pondok Pasantren Al-Jauharen dan Al- As’ad yang ada di Jambi Seberang Kota Jambi. Metode pelaksanaan dilakukan dengan beberapa tahapan, diantaranya penetapan tempat sasaran, survei daerah sasaran, pendataan peserta, pelaksanaan kegiatan, dan evaluasi kegiatan. Kegiatan pelatihan peer counselor dengan beberapa sesi diantaranya; Pertama, Brainstorming Perilaku yang Membutuhkan Bantuan. Kedua, permainan untuk meningkatkan antusiasme peserta, Ketiga, Pemberi materi tentang Peer counseling, teknik dalam melakukan peer counselor, serta pemahaman santri terhadap identifikasi permasalah yang harus ditangani oleh santri sendiri, serta mana masalah yang harus melibatkan tenaga professional. Kegiatan pelatihan peer counselor berjalan efektif sesuai dengan yang direncakan, peserta sangat antusias untuk mengikuti setiap rencana kegiatan, dan mereka mampu memahami dan menerapkan konseling teman sebaya (peer counselor). Kata kunci: pesantren, peer counselor, pelatihan